2018
DOI: 10.1177/0950422218774974
|View full text |Cite
|
Sign up to set email alerts
|

Innovation policy in Russia and the development of university–industry linkages

Abstract: All the major science and innovation activity indicators for Russia have remained largely unchanged over the past 10–15 years. Expenditures on research and development (R&D) have stayed at a low level, with 70% of the funding provided by the federal government. During the last 7 years, the Russian government has introduced a number of instruments to improve research performance and stimulate closer cooperation between universities and companies. This article presents the results of a survey conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…However, NTI centres do not have sufficient shared facilities and equipment, which participants could use for the development and testing of new goods and services. However, the initiative is unavailable to all participants as it only covers a limited number of organisations in particular fields that concentrate main activities and resources within the framework of the NTI (Dezhina, 2018). There is a lack of mechanisms that ensure cooperation and, hence, incentives to build close innovative ties between participants.…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%
“…However, NTI centres do not have sufficient shared facilities and equipment, which participants could use for the development and testing of new goods and services. However, the initiative is unavailable to all participants as it only covers a limited number of organisations in particular fields that concentrate main activities and resources within the framework of the NTI (Dezhina, 2018). There is a lack of mechanisms that ensure cooperation and, hence, incentives to build close innovative ties between participants.…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%
“…The analysis proved that forms and models of cooperation between business and research are mainly determined by the company's general profile and industry affiliation. Inconsistency of state policy, remaining high risks and insufficient funding as well as the low level of the developer organization's research and technical results readiness for practical implementation were identified as the most significant problems of interaction (Bychkova, 2016;Yusupova, 2017;Dezhina, 2018).…”
Section: Research Of Various Intermediaries' and Intermediate Actors'mentioning
confidence: 99%
“…Для компаний более предпочтительным является проведение НИОКР своими силами и ресурсами без постановки заданий университетам и внешним научноисследовательским центрам, поскольку те, как считается, сталкиваются с затруднениями при передаче технологий на необходимом уровне новизны, готовности к внедрению и конкурентоспособности. Вузы и НИИ демонстрируют недостаточную прозрачность и предсказуемость в реализации НИОКР; их способность интегрироваться в функционирующие процессы; их восприятие потребностей и целей делового партнера и его технологий, сроков и требуемых результатов [3].…”
Section: рис 1 структура расходов на технологические инновации крупunclassified